2011
DOI: 10.1002/oti.322
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Time Perception in Young and Elderly People during Jigsaw Puzzle Tasks with Different Complexities

Abstract: We investigated the relationship between time perception during tasks and subjective feelings in young and elderly people. Simple and complex jigsaw puzzles were given to healthy young and elderly subjects. The subjects were asked to estimate the time they had taken to complete the tasks after performing them. The ratio of the subjective to actual duration of time, the duration judgment ratio (DJR), and the relationship between the DJR and the subjective feelings during the tasks were analysed. The elderly gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In their study, self-regulators estimated that the task took significantly longer than nonregulators. Finally, Iwamoto and Hoshiyama (2011) demonstrated that task complexity is an important factor in time perception. All other things being equal, more complex tasks are experienced as taking longer than less complex tasks.…”
Section: We Also Have Fun When Time Fliesmentioning
confidence: 97%
See 4 more Smart Citations
“…In their study, self-regulators estimated that the task took significantly longer than nonregulators. Finally, Iwamoto and Hoshiyama (2011) demonstrated that task complexity is an important factor in time perception. All other things being equal, more complex tasks are experienced as taking longer than less complex tasks.…”
Section: We Also Have Fun When Time Fliesmentioning
confidence: 97%
“…Recent research has demonstrated that this is more than just a saying. For a variety of reasons, enjoyable experiences are felt to pass more quickly than unpleasant (or less pleasant) ones (Droit-Volet & Meck, 2007;Gable & Poole, 2012;Iwamoto & Hoshiyama, 2011). For example, Iwamoto and Hoshiyama (2011) found that participants who reported more interest in completing a 24-piece jigsaw puzzle also felt the puzzle-solving task to pass more quickly than did participants who reported little interest in the task.…”
Section: Time Flies When We Are Having Funmentioning
confidence: 99%
See 3 more Smart Citations